Microgrid network design and control - Selvam, Murugaiah. (2011)
Microgrids comprise low-voltage distribution systems with distributed energy resources (DER) such as Wind, Solar and Fuel cell and controllable loads which can operate connected to the grid or islanded in a controlled coordinated way. This concept aims to move from connect and forget philosophy towards an integration of DER. Microgrids provide clear economic and environmental benefits for end-customers, utilities and society. However, their implementation poses great technical challenges, such as a protection of Microgrid.